2005
DOI: 10.1590/s0074-02762005000400010
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of extracts obtained from Stryphnodendron adstringens on Herpetomonas samuelpessoai

Abstract: We report the effect of Stryphnodendron adstringens on the trypanosomatid Herpetomonas samuelpessoai. The parasites were grown at 28ºC in a chemically defined medium containing crude extract and fractions at concentrations from 100 to 5000 µg/ml obtained from S. adstringens. Concentrations of 500, 1000, 2500, and 5000 µg/ml both crude extract and semi-purified fraction progressively inhibited the protozoans' growth. At a concentration of 100 µg/ml, crude extract or a semi-purified (F3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 11 publications
1
16
0
3
Order By: Relevance
“…In contrast traditional medicines, including herbal and glandular products, appear to address the cause of many diseases and yield superior clinical results. Therefore, crude plant extracts in the form of decoction, infusion or tincture are traditionally more used by the population for the treatment of several diseases, as well as an antiinflammatory and healing agent (Holetz et al, 2005). As a general rule crude therapeutic products are less toxic than their synthetic counterparts because they contain the total family of medicinal compounds (known and unknown) just as they are found in their natural source and hence offer less risk of side effects.…”
Section: Crude Extractsmentioning
confidence: 99%
“…In contrast traditional medicines, including herbal and glandular products, appear to address the cause of many diseases and yield superior clinical results. Therefore, crude plant extracts in the form of decoction, infusion or tincture are traditionally more used by the population for the treatment of several diseases, as well as an antiinflammatory and healing agent (Holetz et al, 2005). As a general rule crude therapeutic products are less toxic than their synthetic counterparts because they contain the total family of medicinal compounds (known and unknown) just as they are found in their natural source and hence offer less risk of side effects.…”
Section: Crude Extractsmentioning
confidence: 99%
“…Extracts of the stem bark from species of Stryphnodendron have several medically useful properties, such as antiinflammatory (Melo et al, 2007), antimicrobial Ishida et al, 2006), antiulcerogenic (Audi et al, 1999), trypanocidal (Holetz et al, 2005) Mello et al (1996a;1996b, who isolated 23 compounds from these tannins. Recently, Lopes et al (2008) reported five new compounds from stem bark of S. adstringens and S. polyphyllum.…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of the stem bark from species of Stryphnodendron have several medically useful properties, such as antiinflammatory (Melo et al, 2007), antimicrobial Ishida et al, 2006), antiulcerogenic (Audi et al, 1999), trypanocidal (Holetz et al, 2005), antioxidant and cicatrizant properties, probably because of their high tannin content (about 20%) (Audi et al, 2004). The content of tannins in Stryphnodendron adstringens was demonstrated by Mello et al (1996a;1996b, who isolated 23 compounds from these tannins.…”
Section: Introductionmentioning
confidence: 99%
“…Species of this genus are utilized in popular medicine for leukorrhea and gynecologic problems, as an antibacterial, antihemorrhagic, antihypertensive or antiulcerogenic, for diarrhea and inflammatory processes, as an astringent, antiseptic or diuretic and for cleansing and healing of wounds, especially in the form of a decoction (Vasconcelos et al, 2004;Souza et al, 2007). The biological studies of the genus show that Stryphnodendron has several activities: antimicrobial (Sanches et al, 2005), antiulcer (Rodrigues et al, 2008), antiviral (Felipe et al, 2006), trypanocidal (Holetz et al, 2005) and against Candida albicans (Ishida et al, 2006).…”
Section: Research Articlementioning
confidence: 99%